Insights Into Water Mass Origins in the Central Arctic Ocean From In‐Situ Dissolved Organic Matter Fluorescence. Issue 7 (7th July 2021) - Stedmon, Colin A.; Amon, Rainer M. W.; Bauch, Dorothea; Bracher, Astrid; Gonçalves‐Araujo, Rafael; Hoppmann, Mario; Krishfield, Richard; Laney, Samuel; Rabe, Benjamin; Reader, Heather; Granskog, Mats A.
Abstract: The Arctic Ocean receives a large supply of dissolved organic matter (DOM) from its catchment and shelf sediments, which can be traced across much of the basin's upper waters. This signature can potentially be used as a tracer. On the shelf, the combination of river discharge and sea‐ice formation, modifies water densities and mixing considerably. These waters are a source of the halocline layer that covers much of the Arctic Ocean, but also contain elevated levels of DOM. Here we demonstrate how this can be used as a supplementary tracer and contribute to evaluating ocean circulation in the Arctic. A fraction of the organic compounds that DOM consists of fluoresce and can be measured using in‐situ fluorometers. When deployed on autonomous platforms these provide high temporal and spatial resolution measurements over long periods. The results of an analysis of data derived from several Ice Tethered Profilers (ITPs) offer a unique spatial coverage of the distribution of DOM in the surface 800 m below Arctic sea‐ice. Water mass analysis using temperature, salinity and DOM fluorescence, can clearly distinguish between the contribution of Siberian terrestrial DOM and marine DOM from the Chukchi shelf to the waters of the halocline. The findings offer a new approach to trace the distribution of Pacific waters and its export from the Arctic Ocean. Our results indicate the potential to extend the approach to separate freshwater contributions from, sea‐ice melt, riverine discharge and the Pacific Ocean. Plain Language Summary: The Arctic Ocean has a layered structure with comparatively warm Atlantic waters (above freezing temperatures) separated from the surface by a cold layer of water called the halocline. This layer allows the surface waters to be cooled sufficiently for sea ice to form. Here we present a new approach to trace the origins of the halocline using organic matter fluorescence as a tracer. These measurements are made from autonomous profiling systems which offer an excellent opportunity to vastly expand our sampling coverage temporally and spatially. Key Points: Arctic surface waters with comparable temperature and salinity have contrasting in situ dissolved organic matter fluorescence Organic matter fluorescence can track low salinity waters feeding into the Transpolar Drift and halocline layers Siberian and Chukchi shelf waters can be separated based on their fluorescence to salinity relationship